Assessing Farmers’ Perceptions of Best Management Practices: An Exploration of the Viewpoints of Cotton and Peanut Farmers in Georgia using Q Methodology - William R Taylor; Abigail Borron; Jessica Holt; Scott Monfort (Journal of Applied Communications, 2024)
While Georgia is one of the top producers of cotton and peanuts in the Unites States, much attention has been centered on ensuring sustainability in the production of these crops. The need to understand what drives farmers’ decision to utilize voluntary best management practices is critical for the improvement of strategies focused on increasing farmers’ adoption of these practices. Empirical evidence that identifies influential factors in farmers’ decision to adopt best management practices have yet to produce consistent predictors of adoption behavior. This has led to increased calls for unique approaches examining how farmers’ views and motivations impact their adoption decisions regarding these practices. This study builds on previous research using Q methodology to provide an in-depth investigation of the differences in farmers’ views on best management practices for cotton and peanut production in southwest Georgia. A purposive sample of 21 participants completed the Q sorting exercise and semi-structured interviews. Analysis of the data revealed three primary viewpoints that were identified and labeled as the: (1) land preservers, (2) ambitious self-starters, and (3) principled go-getters. These perspectives show the differences in motivations for adoption behavior and denote the range of influential factors on farm management decisions. The findings of this study reveal key viewpoints held by Georgia cotton and peanut farmers toward best management practices, which can inform the development of strategically tailored educational resources and opportunities. These targeted educational approaches must account for the specific needs and preferences of farmers found in this study to potentially increase adoption.
Keywords: Best management practices; Q-methodology; Theory of Planned Behavior; Mixed methods; Farmer perceptions